Enhancing Sustainable MSMEs in Karangpring Village through Developing a Green Accounting-based Village Product Bank Model - Oktaviani, Siska Aprilia; Prillinaya Yudhistira; Candra Pramula Pinandita; Dwi Indriani Fidiastutik Wijaya; Ponti Primastuti Aulia Nugraheni (International Journal of Studies in Social Sciences and Humanities, 2026)
Sustainable development requires a balance between economic, social, and environmental dimensions. Green accounting emerges as an approach that internalizes environmental impacts into economic practices. However, its implementation has largely been explored at the corporate level, while studies at the village and MSME institutional scale remain limited. This study focuses on Karangpring Village, Jember, which hosts three key MSME sectors (batik, rose farming, and coffee) but faces challenges such as limited capital, weak marketing capacity, and restricted market access. This research proposes a village product bank model based on green accounting as a collective institution that integrates production management, marketing, and environmentally conscious financial recording to address these issues. A descriptive qualitative approach is employed to explore socio-economic dynamics and the feasibility of green accounting adoption in MSMEs at the village level. The novelty of this research lies in: (1) developing a model for integrating green accounting within village-scale institutions; (2) formulating green accounting indicators tailored for MSMEs; and (3) fostering a collaborative ecosystem among MSME sectors that opens opportunities for linkage with green financing schemes. The proposed model is expected to serve as a replicable framework for other villages in strengthening inclusive and sustainable local economic governance.